A Review on Various Techniques of Image Compression (International Journal of Engineering and Computer Science, 2016)
Images are an important form of data and are used in almost every application. Some applications cannot use images directly due to the large amount of memory space needed to store these images. Image compression is to reduce irrelevance and redundancy of the image data in order to be able to store or transmit data in an efficient form.  Compression of images plays an important role in storing the images .in this paper.  In this paper we analyze different types of existing method of image compression. Now there is question may be arise that how to image compress and which types of technique is used. Basically lossy and lossless image compression technique are used for compress the images.